Alginate as A Natural Coagulant-Aid: Advances, Challenges, and Applications - Kristianto, Hans; Prasetyo, Susiana; Sugih, Asaf Kleopas (Pandawa Institute, 2025)
Coagulation is a critical step in water and wastewater treatments that is essential for the removal of suspended solids, organic matters, and colloidal particles. Conventional metal-based coagulants such as aluminium sulphate, ferric chloride, and polyaluminium chloride and synthetic polymer such as polyacrylamide are widely used due to their proven efficiency. However, concerns over their environmental impact, including the generation of non-biodegradable sludge, potential health risks, and negative impact on the water ecosystem, have driven the search for alternative, eco-friendly coagulants. Natural coagulants derived from plants, animals, or microorganisms have emerged as promising alternatives, offering advantages like biodegradability, non-toxicity, and lower sludge production. Among these, polysaccharide-based coagulants such as alginate, a biopolymer sourced from brown seaweed and bacteria, have gained significant attention. Alginate's biodegradability, non-toxicity, low cost, and versatile gelation properties make it a potential substitute for synthetic coagulants. This review focuses on the use of alginate as a coagulant-aid, providing an overview of its sources, characteristics, coagulation mechanisms, and variables that affect the coagulation performance. The review also highlights the benefits, challenges, and future research directions for improving the efficiency and scalability of alginate in sustainable water/wastewater treatment processes.